Factors causing illegal renovation in residential building / Chan Zheng and Rubiah Md Zan - Zheng, Chan; Md Zan, Rubiah (2019)
Nowadays Illegal renovation is not a new issue in Klang Valley area. Many residential houses have been extended, refurbished or renovated without approval by Local Authority. Based on complaints received from the house owners they choose to proceed with renovation without proper permit as it is difficult to get approval from Local Authority and the process is expensive.